From customer insight to new service development : Case: Wiima Logistics Oy - Rantanen, Karoliina (fi=Turun yliopisto|en=University of Turku|, 2018)
Customers are seen as a good source of data and information when it comes to new service development. In order to succeed at the market, a new service should be planned and developed in a way that it meets the needs of the customers. By developing customer insight and involving customers in the development process of a new service, companies may create better and more innovative ideas and thus develop service concepts that meet the demand of the market. The purpose of this study is to gain understanding of using customer insights as a part of a new service development process. The aim is to investigate what is the value of customer insight in new service development process, as well as ways to acquire insights and integrate them in the development process of a new service. The theoretical background of the study consists of literature relating to customer insight, customer value and new service development. The study was conducted as a case-study and the empirical part of the study is based on expert interviews that were conducted by interviewing both the case company and its potential customers. Altogether, seven semi-structured interviews were conducted. This study finds that the biggest value of customer insight in new service development is to develop a new service to meet the needs of the target market. By involving customers and potential customers in the development process, companies may both educate the potential users about the new service, as well as enhance the customer relationship by showing respect by listening to the opinions of the customer. Companies may have different ways of acquiring customer insight. The study suggests that both traditional market research methods and deep customer insight methods should be used to get deeper in the processes of the customer and to understand the needs of the customer also in the future. Furthermore, customer insights should be integrated in new service development at different stages of the process from idea generation and concept development to the launch of the new service. The findings of this study enhance the understanding of using customer insights in the development process of a new service. The study provides understanding of the value and meaning of customer insight in new service development and encourages companies to utilize customer insights when developing new services. However, as the study only focuses on the positive aspects of customer involvement, further research on the challenges and risks of using customer insights in the development process of a new service is suggested.